Golden F & F Company - Ag. Mahali, Khairunnisa; Md Ali, Noor Hanizah; Sulampit, Marylynd; Md Raip, Ernie Mastura; Abd Momen, Firdausiah (2009)
This factory of processing and selling Dried bean curd entrepreneur is a new factory of processing Dried bean curd with herb. In addition, it is all about processing and selling the Dried bean curd with added some herb that good for health. Actually, the company produce this kind of Dried bean curd because truly care for people by giving a good food with low content of cholesterol to them. In this business, this company put customer satisfaction first, by produce a good of Dried bean curd with herb. The company's goal is to provide best food that will benefit to customer. Besides that, all the processing and selling, the company uses a very expert manager to handle all the work that related in produce this kind of product. On the other hand, all the work in produce this Dried bean curd done it by systematic management to ensure the cleanliness and health. That means all entire employee will use the glove while they produce the Dried bean curd. Company strives to provide a good and health food to our customer so they can take advantages from our product. The Dried bean curd can reduce some chronic disease like high blood and diabetes. Other than that, the dried bean curd also can help for reduce our cholesterol then it also good for skin. This company has decided to open up a business called Golden F & F Company which processing and selling Dried bean curd entrepreneur where the brands' name of our product is Dried bean curd golden life herb. We are operating partnership form of business. Moreover, we have five partnerships who will contribute capital to set up Golden F & F Company. All of us have our own capabilities and qualification in conducting this business. Besides we also have great working experience in related field and willing to put our best effort, commitment to invest in this business. Furthermore we are hiring employee both full time and part-time to help us in processing and selling the dried bean curd. This is to ensure company business runs smoothly and efficient.